Larvicidal Potential of Microbial Agents Bacillus thuringiensis var. israelensis and Bacillus sphaericus against Mosquito Vectors Prevalent in Arid Areas - Singh, Karam V; Bansal, S K (Annals of Arid Zone, 2016)
Short Communication